Self-Regulated Learing Siswa Kelas XI IPS Pada Mata Pelajaran Ekonomi di SMA Negeri 3 Singaraja - Sari, Ni Kadek Andewi Restila; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2021)
The purpose of this study is to find the students' self-regulated Learning of class XI IPS on Economics subjects at SMA Negeri 3 Singaraja in terms of the dimensions of motives, methods, time, behavior, physical environment and social environment. The type of the research was descriptive study with qualitative approach. The populations were all class of XI IPS at SMA Negeri 3 Singaraja with a total of 103 students. Saturated sampling used in this study, this sampling technique uses the entire study population. The data collection methods used were questionnaires and documentation.  The data analysis technique used was descriptive analysis. The results showed that the students' self-regulated learning of class XI IPS on Economics Subjects at SMA Negeri 3 Singaraja in terms of the dimensions of motives, methods, behavior, physical environment were in a good category, while in terms of time dimensions and social environment were in the category of less well.